Pengaruh Ukuran Perusahaan, Anak Perusahaan, Profitabilitas Dan Opini Audit Terhadap Audit Delay Pada Perusahaan Perbankan Yang Terdaftar Di BEI - Caroline Pangestu; Kevin Kevin; Arie Pratania Putri; Alistraja Dison Silalahi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The objective of this study is to determine the effect of Company Size, Subsidiaries, Profitability, and Audit Opinion on Audit Delay in Banking Companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022.This research is quantitative in nature. The data used is secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The population in this study consists of all banking companies listed on the IDX during the 2020-2022 period, totaling 43 companies. A purposive sampling technique was used, resulting in a sample of 43 companies that met the criteria. From this study, it can be concluded that Company Size, Subsidiaries, Profitability, and Audit Opinion simultaneously have a significant effect on Audit Delay. Company Size partially has a negative and significant effect on Audit Delay, while Subsidiaries, Profitability, and Audit Opinion partially do not have a significant effect on Audit Delay.